The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1177/0300060520952282
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral hematological parameters in women with polycystic ovary syndrome

Abstract: Objective There have been few studies on hematological parameters (e.g., hemoglobin, red cell distribution width, white blood cells, and mean platelet volume), and polycystic ovary syndrome (PCOS). This study aimed to compare hematological parameters between women with PCOS and controls. Methods We performed an age-matched case–control study in Faisal bin Mishal Center for Infertility, Buraidah (Kingdom of Saudi Arabia). The cases were women with PCOS and an equal number of healthy women were enrolled as contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The results of this study were consistent with a study which reported that PCOS is the most common endocrine disorder among women between the ages of between (20-40) years .Our results similar to previous study by [13] there were no significant differences in age, residence, and education between the cases and the controls. While our results contradicted with study by [15] which found an association between body mass index and PCO.…”
Section: Discussionsupporting
confidence: 92%
“…The results of this study were consistent with a study which reported that PCOS is the most common endocrine disorder among women between the ages of between (20-40) years .Our results similar to previous study by [13] there were no significant differences in age, residence, and education between the cases and the controls. While our results contradicted with study by [15] which found an association between body mass index and PCO.…”
Section: Discussionsupporting
confidence: 92%
“…Their results showed that RDW at a cut-off value of 12.8 had an odds ratio of 3.1 and a 95% CI (1.25-7.6) to predict clomiphene citrate resistance among lean PCOS patients (18). On the other hand, the Alhabardi study found no significant difference between RDW and other blood indices among the PCOS and healthy controls they examined ; the author suggested that the small sample size and the presence of complex interaction between PCOS etiological factors were responsible for the shortcoming of their results (19). Our results showed significantly higher serum testosterone in PCOS cases, which was positively correlated to RDW.…”
Section: Discussionmentioning
confidence: 94%
“…Finally, 10 studies without overlapping patients complied with the inclusion criteria, so were selected for the meta-analysis. 19 28 A flowchart illustrating the study selection process is presented in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%